‘Meta-Choreographies’ Between the Desktop and the Stage - Ariadne Mikou (The International Journal of Screendance, 2022)
How does one re-use pre-existing material in order to form an expanded choreographic practice of relating to audio-visual archive without being considered of stealing or lacking originality? Copying, re-using and appropriation, not innocent from copyright implications but often entrapped in the modernist myth of originality, are practices that have been enhanced by the growth of the digital archive available on the internet and the expansion of the online public space. In light of this surge that challenges the body-to-body dance transmission, this text analyzes copying, re-use and appropriation as forms of citation, both audio-visually and corporeally, through the work of the Italian choreographer, performer, educator and filmmaker Jacopo Jenna who connects fragments of preexisting works to create unexpected visual and corporeal associations that prompt us to re-think the dance canon. His work, based on a meta-choreographic and meta(dance)cinematic technique, moves between screen and stage, two-dimensional and three-dimensional space and brings into dialogue immaterial bodies and gestures stored in our collective memory with flesh bodies on stage. But, what issues and possibilities does this practice of disembodied transmission from screen-to-body entail?
Keywords: appropriation art; body archive; citation; copyright; disembodied transmission; found choreography; found footage; imitation; meta-art